Hiding in plain sight: the Coptic Museum in the Egyptian cultural landscape. Issue 6 (19th September 2019) - Levitt, Peggy; Parrs, Alexandra
Abstract: Museums have long been important tools of nation building and of helping nations deal with their increasing diversity. The Arab Spring of 2011 brought massive social upheaval and change to the Middle East. Egypt experienced particularly dramatic changes. Long-standing fissures around who qualifies as an Egyptian, which groups dominate in this secular or religious nation, and what it means to be an Egyptian today came to the fore. How did different groups fare within this negotiation and what role did cultural institutions play? We explore these struggles through the lens of the Coptic Museum and the experiences of the Coptic community. We argue that the Museum historici s es Copticism, or depicts it as an historical, bounded period in Egyptian history. It also embraces a historical narrative that sees Copts as the direct descendants of the Pharaohs, and therefore the original Egyptians, although some later converted to Islam. By so doing, the Museum positions the community centrally but unchallengingly within the ever-changing 'master' national narrative, whether in its more religious or secular form. By telling this particular story, the community saves itself and its materials, but it also constructs and perpetuates its paradoxically central, but marginal position in the nation.